CCL4 participates in the reprogramming of glucose metabolism induced by ALV-J infection in chicken macrophages - Wu, Huixian; Zaib, Gul; Luo, Huan; Guo, Wang; Wu, Ting; Zhu, Shutong; Wang, Chenjun; Chai, Wenxian; Xu, Qi; Cui, Hengmi; Hu, Xuming (Frontiers in Microbiology, 2023)
Interferon and chemokine-mediated immune responses are two general antiviral programs of the innate immune system in response to viral infections and have recently emerged as important players in systemic metabolism. This study found that the chemokine CCL4 is negatively regulated by glucose metabolism and avian leukosis virus subgroup J (ALV-J) infection in chicken macrophages. Low expression levels of CCL4 define this immune response to high glucose treatment or ALV-J infection. Moreover, the ALV-J envelope protein is responsible for CCL4 inhibition. We confirmed that CCL4 could inhibit glucose metabolism and ALV-J replication in chicken macrophages. The present study provides novel insights into the antiviral defense mechanism and metabolic regulation of the chemokine CCL4 in chicken macrophages.